High-efficiency threshold-less Cherenkov radiation generation by a graphene hyperbolic grating in the terahertz band. (15th October 2021) - Zhang, Xiaoqiuyan; Hu, Min; Zhang, Zhuocheng; Wang, Yueying; Zhang, Tianyu; Xu, Xingxing; Zhao, Tao; Wu, Zhenhua; Zhong, Renbin; Liu, Diwei; Wei, Yanyu; Gong, Yubin; et al.
Abstract: Cherenkov radiation (CR), generated when charged particles move faster than the light velocity in a medium, is an important radiation phenomenon of electron-matter interactions. Here, we demonstrate high-efficiency threshold-less in-plane CR generation in the terahertz (THz) band using a periodic graphene hyperbolic grating (GHG) structure. Our theoretical and numerical analyses proved that the phase velocity in the GHG is always lower than the electron velocity; this is owing to the graphene hyperbolic plasmon polaritons induced biaxially in the GHG. Based on the simulation results, the power of the in-plane CR in the GHG is nearly two orders of magnitude larger than that of the out-of-plane CR in the conventional graphene-dielectric hyperbolic metamaterial bulk. A full electromagnetic dipole source mode is employed to describe the fascinating in-plane hyperbolic-like spatial dispersion in the GHG. Moreover, by adjusting the size of the GHG, graphene chemical potential, and free electron energy, the CR angle and intensity can be completely controlled. This framework provides a new way to develop high-efficiency, threshold-less, and tunable CR sources in the THz range with excellent adjustability and serves as a general approach applicable to other polariton types active in a wide range of materials, such as phonon- and exciton-polaritons. Graphical abstract: Image 1